Clinical Outcomes of Carotid Artery Stenting for Carotid Artery Stenosis in Maintenance Hemodialysis Patients - Shuki OKUHARA; Tomoaki MURAKAMI; Shingo TOYOTA; Kosei OKOCHI; Koichi NAKASHIMA; Kazuhiro TOHARA; Shuhei YAMADA; Takamune ACHIHA; Maki KOBAYASHI; Haruhiko KISHIMA (Neurologia Medico-Chirurgica)
Most previous large studies of carotid artery stenting (CAS) in maintenance hemodialysis patients are old-era, do not describe the types of stents and method of protection, and their effectiveness is unknown. CAS has progressed remarkably, and tailor-made CAS is now possible in hemodialysis patients according to the lesion. We aimed to analyze the outcomes of CAS in maintenance hemodialysis patients treated in our institution. We retrospectively investigated the data of patients who underwent elective CAS in our institution between January 2012 and April 2023. Firstly, we verified the outcomes of CAS in maintenance hemodialysis patients. Secondly, the outcomes of CAS in maintenance hemodialysis patients were compared with CAS in nondialysis patients during the same period. During the study period, 212 patients with carotid stenosis underwent CAS. Among these, 18 patients undergoing maintenance hemodialysis were identified for analysis. All 18 patients underwent lesion-specific tailor-made CAS. All 18 patients were technically successfully stented with good vasodilation and improvement in stenosis. No symptomatic cerebral infarction occurred within 30 days after CAS. There was no difference between dialysis and nondialysis patients in the risk of symptomatic complications and death occurring within 30 days after surgery. There was a higher risk of hemorrhagic complications not associated with prognosis in the dialysis group (23.1% vs 1.0%, P = 0.0047). No in-stent restenosis (>50% stenosis) and ipsilateral cerebral infarction at 1 year occurred during follow-up. CAS in hemodialysis patients may be safe and effective.